2017
DOI: 10.1186/s13075-017-1451-5
|View full text |Cite
|
Sign up to set email alerts
|

Failure to achieve lupus low disease activity state (LLDAS) six months after diagnosis is associated with early damage accrual in Caucasian patients with systemic lupus erythematosus

Abstract: BackgroundThe aim was to assess the attainability and outcome of the lupus low disease activity state (LLDAS) in the early stages of systemic lupus erythematosus (SLE).MethodsLLDAS prevalence was evaluated at 6 (T1) and 18 (T2) months after diagnosis and treatment initiation (T0) in a monocentric cohort of 107 (median disease duration 9.7 months) prospectively followed Caucasian patients with SLE. Reasons for failure to achieve LLDAS were also investigated. Multivariate models were built to identify factors as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
61
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 33 publications
(41 reference statements)
5
61
1
Order By: Relevance
“…Anti‐DNA antibodies, which may identify patients with more severe disease, were associated with a low likelihood of being in LLDAS, analyzing results both cross‐sectionally and longitudinally . Their role in predicting LLDAS failure might also reflect their being part of SLEDAI‐2K items.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Anti‐DNA antibodies, which may identify patients with more severe disease, were associated with a low likelihood of being in LLDAS, analyzing results both cross‐sectionally and longitudinally . Their role in predicting LLDAS failure might also reflect their being part of SLEDAI‐2K items.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Anti-DNA antibodies, which may identify patients with more severe disease, 37 were associated with a low likelihood of being in LLDAS, analyzing results both cross-sectionally and longitudinally. 10,12 Their role in predicting LLDAS failure might also reflect their being part of SLEDAI-2K items. Patients with a history of serositis who escalated their treatment at baseline achieved LLDAS more frequently after 12 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the definitions of low disease activity in SLE, the Lupus Low Disease Activity State (LLDAS) developed by Asia-Pacific Lupus Collaboration was well-validated and widely accepted [9][10][11][20][21][22]. Previous studies had proved that the maintenance of LLDAS during follow-up was associated with a lower frequency of organ damage accrual or flare [14][15][16][22][23][24][25]. Meanwhile, some studies had revealed the associated factors of maintaining LLDAS during follow-up [14,15,[22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%